Hepatocyte-specific loss of GPS2 in mice reduces non-alcoholic steatohepatitis via activation of PPARα - Ning Liang (Nature Portfolio, 2019)
Dysregulation of PPARα dependent fatty acid oxidation promotes hepatic steatosis. Here the authors show that GPS2 inhibits PPARα activity and that ablation of GPS2 ameliorates hepatic steatosis in mice.